2015
DOI: 10.1007/bf03356561
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Cereal Cyst Nematodes (Heterodera spp.) in Wheat and Barley Fields in North-Eastern Regions of Syria

Abstract: Cereal cyst nematodes (CCN) are important plant-parasitic nematodes of wheat and barley, and exist in most of the cereal growing regions of the world. As there is limited information on the nature and distribution of CCN species in Syria, a survey was conducted in north-eastern Syria to assess the distribution of CCN in the main wheat and barley growing areas. In the summer of 2009, a total of 167 composite soil samples were collected from 167 wheat and barley fields. Cysts were extracted from soil using the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Three surveys conducted in Syria revealed H. latipons to be the most dominant species of the H. avenae group (Abidou et al, 2005b;Hassan, 2008;Toumi et al, 2012). However, the results also revealed that mixtures of two (H. avenae with H. latipons or H. avenae with H. filipjevi) or even three species can occur in a same field.…”
Section: Discussionmentioning
confidence: 99%
“…Three surveys conducted in Syria revealed H. latipons to be the most dominant species of the H. avenae group (Abidou et al, 2005b;Hassan, 2008;Toumi et al, 2012). However, the results also revealed that mixtures of two (H. avenae with H. latipons or H. avenae with H. filipjevi) or even three species can occur in a same field.…”
Section: Discussionmentioning
confidence: 99%
“…CCNs can seriously reduce yields of cereal crops, especially in temperate and semi-arid regions (Rivoal and Cook, 1993;Nicol and Rivoal, 2008). To keep the population densities of this parasite below damage levels, appropriate management processes, such as crop rotation, are necessary (Mokabli et al, 2002;Smiley et al, 2007), Crop rotations that include broadleaf crops, corn, fallow, and resistant wheat (Toumi et al, 2015), barley, or oat varieties can greatly reduce the nematode density. In addition, growing susceptible hosts less than 50 % of the time in heavy-textured soils and less than 25 % of the time in light-textured soils could dramatically reduce CCN (Yan and Smiley, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Species distribution maps for representatives of the Avenae group were made using personal communications from colleagues listed in the Acknowledgements and from published sources (Meagher, 1977;Tikhonova, 1978;Abidou et al, 2005b;Holgado et al, 2006;Tanha Maafi et al, 2007;Peng et al, 2009;Pankaj et al, 2011;Dawabah et al, 2012;Mokrini et al, 2012Mokrini et al, , 2017Pridannikov et al, 2015;Toumi et al, 2015a;Li et al, 2016;Tirchi et al, 2016;Cui et al, 2017, and others).…”
Section: Distribution Mapsmentioning
confidence: 99%